2017
DOI: 10.2527/jas.2017.1493
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of carcass and meat quality traits in different muscles (longissimus dorsi and semimembranosus) of Hanwoo (Korean cattle)1

Abstract: We estimated heritability () and genetic and phenotypic correlations for carcass and meat quality traits of longissimus dorsi (LD) and semimembranosus (SM) muscles in 30-mo-old Hanwoo steers. Variance and covariance components were estimated using REML procedures under univariate and bivariate models. The mean carcass weight (CWT), eye muscle area (EMA), back fat thickness (BFT), and marbling score (MS) were 428.20 ± 46.30 kg, 87.38 ± 8.54 cm2, 13.00 ± 5.14 mm, and 5.21 ± 1.56, respectively. The mean CIE refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
7
7
1
Order By: Relevance
“…In the present study we evaluated, for the first time, the genetic parameters of KR and RGR (indirect measures of feed efficiency) and their correlations with growth and carcass traits in Hanwoo beef cattle. Table 2 In the present study, the heritability estimates for carcass traits were in accordance with most of the previous studies in Hanwoo cattle [12,14,18], except those of Kim et al [11] and Bhuiyan et al [13]. These disagreement in the heritability estimates may be due to differences in slaughter age of animals measured which likely leading to differences in the structure of data among Hanwoo populations.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study we evaluated, for the first time, the genetic parameters of KR and RGR (indirect measures of feed efficiency) and their correlations with growth and carcass traits in Hanwoo beef cattle. Table 2 In the present study, the heritability estimates for carcass traits were in accordance with most of the previous studies in Hanwoo cattle [12,14,18], except those of Kim et al [11] and Bhuiyan et al [13]. These disagreement in the heritability estimates may be due to differences in slaughter age of animals measured which likely leading to differences in the structure of data among Hanwoo populations.…”
Section: Resultssupporting
confidence: 90%
“…As depicted in Table 3, the moderate, positive genetic correlations (0.55) between CW and EMA obtained in our study are similar to the results of Choi et al [12] and Bhuiyan et al [13], which were 0.52 and 0.60, respectively, but disagree with the findings of Kim et al [11] and Do et al [32], who reported lower (0.07) or greater (0.80) genetic correlations, respectively than our results for Hanwoo cattle. Additionally, positive genetic (0.52 and 0.45, respectively) and phenotypic (0.44 and 0.39, respectively) correlations between CW and EMA shown by [19,20] in Brahman cattle.…”
Section: Correlations Among the Traitssupporting
confidence: 92%
See 1 more Smart Citation
“…The carcass and meat quality traits investigated in this study were CWT, EMA, BFT, and MS. Feeding, management, and trait measurements were according to Bhuiyan et al (2017) . Briefly, the cold CWT was taken after chilling for about 24 h. Longissimus dorsi muscle samples (approximately 1.5 kg) were collected from the junction between the 12th and 13th rib for the EMA, MS, and BFT measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Meat quality phenotypes in beef cattle are economically important traits which are quantitative in nature with usually low to medium genetic control [1,2]. Multiple efforts have been directed to identify genes able to explain part of the phenotypic variability present in meat quality related traits in different populations [3][4][5].…”
Section: Introductionmentioning
confidence: 99%